A Fractional Trust Region Method for Linear Equality Constrained Optimization - Honglan Zhu; Qin Ni; Liwei Zhang; Weiwei Yang (Discrete Dynamics in Nature and Society)
A quasi-Newton trust region method with a new fractional model for linearly constrained optimization problems is proposed. We delete linear equality constraints by using null space technique. The fractional trust region subproblem is solved by a simple dogleg method. The global convergence of the proposed algorithm is established and proved. Numerical results for test problems show the efficiency of the trust region method with new fractional model. These results give the base of further research on nonlinear optimization.